Studi Kelayakan Kompetensi Profesional Guru Di Madrasah Ibtidaiyah Muhammadiyah 2 Riau - Yusuf Fendra; Anissa Rahmi; Yossi Pratiwi; Zainab Lailatil Zakir; Rahmi Dayati; Sakban Sakban (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Teacher competency is very important, so a teacher must have the ability to professionally improve the implementation of their duties in the field of education. This is useful for educating the nation's children. This feasibility study aims to formulate policies related to improving the quality of education which is focused on the conditions of adequate madrasah ibtidaiyah (MI) teachers based on the professional competence possessed by each teacher. This research uses qualitative methods with cross sectional techniques to analyze data for each MI teacher based on academic qualifications according to the field of study they teach. The findings of this research show that there are still many MI teachers who do not have undergraduate academic qualifications as stipulated in Law No. 14 of 2005 concerning Teachers and Lecturers. The ratio between the number of elementary schools (SD) and MI (both private and public) in Tampan District is 5:1; or the number of elementary schools is 41 consisting of 31 state elementary schools and 10 private elementary schools, while the number of new MIs is 8, all of them have private status. It can be argued that public interest and the government's response to MI is still relatively low due, among other things, to the relative lack of competent teachers.